The antagonistic relationship between apoptosis and polyploidy in development and cancer - Herriage, Hunter C.; Huang, Yi-Ting; Calvi, Brian R. (Seminars in cell & developmental biology, 2024)
One of the important functions of regulated cell death is to prevent cells from inappropriately acquiring extra copies of their genome, a state known as polyploidy. Apoptosis is the primary cell death mechanism that prevents polyploidy, and defects in this apoptotic response can result in polyploid cells whose subsequent error-prone chromosome segregation are a major contributor to genome instability and cancer progression. Conversely, some cells actively repress apoptosis to become polyploid as part of normal development or regeneration. Thus, although apoptosis prevents polyploidy, the polyploid state can actively repress apoptosis. In this review, we discuss progress in understanding the antagonistic relationship between apoptosis and polyploidy in development and cancer. Despite recent advances, a key conclusion is that much remains unknown about the mechanisms that link apoptosis to polyploid cell cycles. We suggest that drawing parallels between the regulation of apoptosis in development and cancer could help to fill this knowledge gap and lead to more effective therapies.